2020
DOI: 10.1016/j.fitote.2020.104706
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyisoquinoline alkaloids from the leaves of Androcymbium palaestinum

Abstract: Thirteen compounds were isolated from the methanolic extract of the leaves of Androcymbium palaestinum Baker (Colchicaceae). Of these, three were new, two were new natural products, and eight were known. The new isolated compounds were (+)-1-demethylandrocine (5), (−)andropalaestine (8), and (+)-2-demethyl-β-lumicolchicone (10), while the new natural products were (+)-O-methylkreysigine-N-oxide (3) and (+)-O,O-dimethylautumnaline (9). Moreover, two known compounds are reported for the first time from this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When tested for potency in OVCAR3 cells, they found the amino methylated naturally occurring analogue (IC 50 = 77 nM) of colchicine to be 3 fold less potent than colchicine (IC 50 = 23 nM) but 10 fold more potent than the de-methoxy naturally occurring analogue (IC 50 = 2230 nM). 98 Another SAR study tested in ovarian cancer cells SKOV3 found 7-deacetyl-10-alkyl thiochochicine derivatives displayed significantly better potency than the natural product. The C10 thiomethane derivative displayed the most potent activity in SKOV3 cells with an IC 50 of 1.3 nM.…”
Section: Recent Studies On Botanical Nps and Associated Drug Developm...mentioning
confidence: 99%
See 1 more Smart Citation
“…When tested for potency in OVCAR3 cells, they found the amino methylated naturally occurring analogue (IC 50 = 77 nM) of colchicine to be 3 fold less potent than colchicine (IC 50 = 23 nM) but 10 fold more potent than the de-methoxy naturally occurring analogue (IC 50 = 2230 nM). 98 Another SAR study tested in ovarian cancer cells SKOV3 found 7-deacetyl-10-alkyl thiochochicine derivatives displayed significantly better potency than the natural product. The C10 thiomethane derivative displayed the most potent activity in SKOV3 cells with an IC 50 of 1.3 nM.…”
Section: Recent Studies On Botanical Nps and Associated Drug Developm...mentioning
confidence: 99%
“…97 One recent colchicine SAR campaign that tests their analogues an in ovarian cancer cell lines is from El-Elimat and co-workers. 98 El-Elimat and coworkers isolated (−)-colchicine in a new species, Androcymbium palaestinum. When tested for potency in OVCAR3 cells, they found the amino methylated naturally occurring analogue (IC 50 = 77 nM) of colchicine to be 3 fold less potent than colchicine (IC 50 = 23 nM) but 10 fold more potent than the de-methoxy naturally occurring analogue (IC 50 = 2230 nM).…”
Section: Toxicity (T)mentioning
confidence: 99%
“…As part of an ongoing project to uncover new chemistry from nature [1], [2], [3], [4], [5], our group has been investigating freshwater fungi [6], [7], [8], [9], [10], [11]. Lignicolous freshwater fungi represent a viable resource for discovering new secondary metabolites with a broad range of biological activities [12], [13], [14].…”
mentioning
confidence: 99%